Research on the Microscopic Adsorption Characteristics of Methane by Coals with Different Pore Sizes Based on Monte Carlo Simulation - Chunhua Zhang; Yuqi Zhai (Applied Sciences)
In order to explore the influence of different pore sizes of anthracite on the methane adsorption characteristics, a low-temperature liquid nitrogen adsorption experiment was carried out. Six types of anthracite with pore sizes ranging from 10 Å to 60 Å were selected as simulation objects. By means of molecular simulation technology and using the Materials Studio 2020 software, a macromolecular model of anthracite was established, and a grand canonical Monte Carlo (GCMC) simulation comparative study was conducted. The variation laws of the interaction energy and diffusion during the process of coal adsorbing CH4 under different pore size conditions were obtained. The results show that affected by the pore size, under the same temperature condition, the peak value of the interaction energy distribution between coal and CH4 shows a downward trend with the increase in the pore size under the action of pressure, and the energy gradually decreases. The isothermal adsorption curves all conform to the Langmuir isothermal adsorption model. The Langmuir adsorption constant a shows an obvious upward trend with the increase in the pore size, with an average increase of 16.43%. Moreover, under the same pressure, when the pore size is 60 Å, the adsorption amount of CH4 is the largest, and as the pore size decreases, the adsorption amount also gradually decreases. The size of the pore size is directly proportional to the diffusion coefficient of CH4. When the pore size increases to 50 Å, the migration state of CH4 reaches the critical point of transformation, and the diffusion coefficient rapidly increases to 2.3 times the original value.